Indeks Kedalaman Kemiskinan Sebelum dan Saat Pandemi Covid-19 di Indonesia - Umar Habib; Heru Wahyudi (Penerbit Goodwood, 2022)
Purpose: This study aims to determine whether or not there are differences in poverty gap index before and during the COVID-19 pandemic. Research methodology: The analytical method used is descriptive statistical analysis and proven by the T-test Paired Sample Two Tests for Means, to poverty gap index data (P1) 2018S1-2021S2 in 34 provinces. Results: The results showed that there were differences in poverty gap index before and during the COVID-19 pandemic. This is indicated by the value of the Paired Two Sample for Means T-test, which has a t-statistic value smaller than t-critical, namely -5.2028 < 9776. According to poverty gap index ranking, there are 5 provinces that have the highest poverty gap index in the same order before and during the COVID-19 pandemic, like a Papua, West Papua, Nusa Tenggara, Maluku, and Gorontalo. Limitations: The limitation in this study is only used statictics descriptive method. Contribution: The results of this study are expected to be a reference for the government in terms of equitable distribution of social assistance by adding a poverty gap index variable to strengthen the poverty line index variable.